Exploring Diverse Effects of Four Types of Mobility on University Entrepreneurship - Satoko Yasuda (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2016)
This study explores the mechanism by which mobility influences university entrepreneurship through an empirical analysis of Japanese scientists working for the University of Tokyo. It presents theory-driven typology of mobility and applies it to the knowledge-transfer context. First, this paper subdivides previously-studied mobility into four types – job mobility (JM), sector mobility (SM), international mobility (IM), and the educational background mobility (EBM). Then, it empirically shows that both JM and IM have positive and significant correlation with university entrepreneurship, whereas neither SM nor EBM does. Based on the result, this study discusses that JM and IM accelerate the formation of skills necessary for the commercialization of university research; however, SM and EBM may have no impact on it.